Pengembangan Mobile Learning berbasis Android menggunakan Metode Mobile-D (Studi Kasus: SD Negeri Wates Kabupaten Kediri) - Giri Nugroho; Komang Candra Brata; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
During the COVID-19 pandemic, the Directorate General of Higher Education urges learning activity to be done from home. Learning activities during the pandemic at SD Negeri Wates were carried out through a messaging service application on Android devices. More than 70% of teachers at SD Negeri Wates do not have laptops to support the learning process and 98.5% of students use Android devices. The absence of face-to-face interaction during the pandemic has reduced student scores and 17-28% of students admitted they did not understand the material given. Teachers also have difficulty in preparing K13 report cards, recapitulating student assignments, and obtaining and disseminating school information. The purpose of this research is to develop a mobile learning application by adjusting the needs and providing ease of operation. The method that will be used is Mobile-D because Mobile-D has flexible agile-like properties and is a suitable methodology for making mobile applications with a team of fewer than 10 people and the process can be done in less than 10 weeks. Data was collected through interviews and questionnaires. Based on the results of the research conducted, the user's assessment of the application with an average score of 83.9 on the teacher side and 87.3 on the student side. This figure proves that the application has excellent effectiveness, efficiency, and satisfaction.